2006
DOI: 10.1117/12.703228
|View full text |Cite
|
Sign up to set email alerts
|

Widely tunable long-period waveguide grating filters

Abstract: This paper presents a review of the development of long-period waveguide gratings (LPWGs) with focus on the realization of various kinds of tunable devices, such as band-rejection filters, variable attenuators, band-pass filters, and add/drop multiplexers. A number of specific examples are given to demonstrate how the geometry and material flexibility of the optical waveguide technology facilitates the design of widely tunable LPWG-based devices. LPWG is evolving into a versatile waveguide structure for the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Recently, it has been reported that the waveguide coupler based on long-period waveguide grating (LPWG) could achieve 75 nm tuning range and realize thermal tuning [7][8][9]. Though the tuning speed is still slow and the FWHM of passband of this coupler is as wide as about 4 nm, it has potential to become a novel high performance filter.…”
mentioning
confidence: 99%
“…Recently, it has been reported that the waveguide coupler based on long-period waveguide grating (LPWG) could achieve 75 nm tuning range and realize thermal tuning [7][8][9]. Though the tuning speed is still slow and the FWHM of passband of this coupler is as wide as about 4 nm, it has potential to become a novel high performance filter.…”
mentioning
confidence: 99%